Visualisasi Iklan Media Cetak KPK sejak Masa Berdiri hingga ‘Serangan Koruptor’ - Hendy Yuliansyah (LP2M ISBI Bandung, 2012)
Corruption is every nation’s problem in all over the world, including Indonesia. Classified as an extraordinary crime, Komisi Pemberantasan Korupsi (KPK) were established to eradicate it. In order to implement its tasks, it campaignes in several kind of media including printed advertisement. At first of its establishment, KPK was ambitiously active to prevent and crack corruption to whole com- munity level including the state officials. However, when KPK was criminalized, and lizard against alligator, public opinions stated that it was a counter attack from the corruptors. This condition has affected its printed advertisement, which was designed and produced by itself. The research shows that its visualization has been changed, from its first editions up to the corruptor’s attack phase. The changes included message, color, illustration and typhography. Keywords: visualization, advertisement, mass media, KPK.